Demographic and theoretical variables in the age-period-cohort analysis of illegal behavior - Menard, Scott W. (Journal of research in crime and delinquency, 1992)
The article presents a study on the cohort analysis of illegal behavior in demographic and theoretical variables. Concern with aggregate patterns of deviant and illegal behavior has characterized criminology from its inception. The existence of a nonlinear relationship between age and illegal behavior is well-established in the literature on illegal behavior, but there appears to be no consensus on the reason for that relationship. Illegal behavior may reach a maximum rate at different ages for different offenses: around age 15 or 16 for many property crimes; earlier for some violent offenses, and later, perhaps around age 15 or 16 for illegal drug use and some victimless or consensual offenses. First, in all ten of the equations, substitution of delinquent bonding for age resulted in a statistically significant coefficient for delinquent bonding, and in 9 of the 10 equations, inclusion of both age and delinquent bonding in the combined analysis resulted in the elimination of age from the combined equation